RESPONSE MODELLING OF NIMBY ACTUATOR IN PHYSICAL SIMULATION SOFTWARE WITH ROS FRAMEWORK - Maulana, Irvan
Legged robots have the advantage of flexibility in motion with the disadvantage of more complex motion control than wheeled robots. In a wheeled robot, the majority of the movement is carried out by providing a certain vector velocity according to the robot's construction, while in a legged robot, it is necessary to generate a motion pattern and a phase difference between one leg and another. The complexity of this motion makes the development of a legged robot difficult to do, especially from the construction of the leg shape, the selection of actuators, and the generation of the motion pattern itself. This article discusses a software architecture system that can be easily developed and can be simulated synchronously with the real actuator system that will be used on the development of robot leg. To do this, we need a system that can send input to the simulator and communicate with the hardware that will be part of the four-legged robot to be developed. The system that has been built is part of the development of “Dombabot”, a fourlegged robot. Part of Dombabot robot system discussed in this document are simulation and software system. To make sure continuation development of this robot, ROS framework has been used as backend communication for each process. All of these processes are proven to successfully extracted send 12 joint data to both hardware and simulation system of this robot. To replicate Dombabot dimension in for simulation purpose, urdf file format is used and verified in Gazebo, a physical simulation software. However, our methods to tune PID parameter to replicate the exact response of the real actuator has not showed satisfied result because the lack of internal parameter taken into our model.